Wisconsin Environmental Law Handbook - Best, Michael (Government Institutes, 2007)
Telecommunications With nearly 50 professionals at the cutting edge of our fields, it is our priority to know and fully understand our clients' business by keeping abreast of industry trends and practices. We are regular presenters and panelists at industry and legal seminars and conferences. We actively participate in environmental public policy development by serving on advisory committees appointed by the Governor, the Secretaries of DATCP, DNR and DOR, and the Legislature.